Problems and Perspectives of Forensic Examination of Dactyloscopic Origin’s Traces (Law and Safety, 2020)
The current state of problems of examining traces of dactyloscopic origin has been analyzed. It has been determined that the perspective of forensic examination of dactyloscopic origin’s traces depends on the correct work with such traces at the crime scene. It has been noted that one should follow general and special recommendations in order to ensure further quality expert examination and identification of the person by handprints during the crime scene search.The main problems of detection, fixation and packing the handprints, which are due to objective and subjective reasons: intensive and stressful work at the crime scene, inadequate forensic provision of law enforcement agencies, lack of staff, low qualification of forensic inspectors, negligence in the performance of official duties by authorized persons. Two ways of obtaining handprints have been identified: during the crime scene search and during dactyloscopic registration of persons.Suggestions for solving problems of examining the traces of dactyloscopic origin have been provided. It has been proved that they should be solved comprehensively at the national level: by improving the logistics of law enforcement agencies, improving the quality of training of highly qualified personnel for forensic investigation units, improving the procedure for introducing the latest advances in science and technology into expert and forensic activities.The author has distinguished the perspective areas of work with handprints. It has been noted that one of the priority areas of work of law enforcement agencies and the Expert Service should be the purposeful development and implementation of perspective methods of work with traces of dactyloscopic origin.
Keywords: dactyloscopy; traces of dactyloscopic origin; problems of work with traces; perspectives of dactyloscopic examinations